2009
DOI: 10.1007/s11255-009-9666-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients on maintenance dialysis

Abstract: Disorders of bone and mineral metabolism affect almost all patients with advanced chronic kidney disease (CKD). High prevalence of decreased bone mineral density has been reported in this population; however, the role and diagnostic utility of bone density measurements are not well established. The incidence of bone fractures is high in patients with ESRD, but the association between fractures and bone density is not obvious. A recent meta-analysis suggested that decreased density at the radius might be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 118 publications
0
18
1
2
Order By: Relevance
“…In this study, of the 20.3% elderly people who were part of the sample, the prevalence of a history of falls in this group was 30.7% related to the adults. Although the percentage found was relatively lower than those of the aforementioned studies 18,19 , it was still higher than the percentage in the group of adults in the sample (13.7%).…”
Section: Fallscontrasting
confidence: 71%
See 1 more Smart Citation
“…In this study, of the 20.3% elderly people who were part of the sample, the prevalence of a history of falls in this group was 30.7% related to the adults. Although the percentage found was relatively lower than those of the aforementioned studies 18,19 , it was still higher than the percentage in the group of adults in the sample (13.7%).…”
Section: Fallscontrasting
confidence: 71%
“…high 18 . In a study conducted with patients on hemodialysis, the researchers observed a history of falls in 47% of them, with an average of 1.60 fall per person/ year, and the mortality rate directly associated with falling was 4% 19 . In this study, of the 20.3% elderly people who were part of the sample, the prevalence of a history of falls in this group was 30.7% related to the adults.…”
Section: Fallsmentioning
confidence: 99%
“…This is true for aluminium bone disease as well [8]. As low BMD may be associated with all subtypes of ROD, although relatively higher BMD has been reported with adynamic bone disease [9,10], BMD by DEXA is unlikely to be sensitive or specific to either diagnose or differentiate osteoporosis from other disorders of ROD. Furthermore, the higher prevalence of abdominal aortic calcification and the differential effect of PTH on trabecular and cortical bones may also confound the interpretation BMD in CKD [9].…”
Section: Diagnosis Of Osteoporosis and Fracture Risk Assessmentmentioning
confidence: 99%
“…Bone mineral metabolism is dysregulated in chronic kidney disease (CKD) patients starting from the early stages [3]. In extensive studies done on this population it is determined that dysregulated bone mineral metabolism is closely associated with increased risk of hi p fracture, cardiovascular disease and increased morbidity and mortality risk [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%